Analisis pendapatan pedagang pasar tradisional di Kota Kuala Tungkal Kabupaten Tanjung Jabung Barat (studi kasus pasar ikan parit 2) - Muhamad Yoza Hermanzah; Rahma Nurjanah; Erni Achmad (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2020)
This study aims to analyze the income of Traditional Market Traders in the Trench 2 Market, Tungkal Ilir District, Tanjung Jabung Barat District. The data used in this study are primary data, the sampling method used in this study is Purposive Sampling with 20 respondents of fish traders, the analytical tool used is Multiple Linear Analysis. Based on the results of the study obtained a probability value of 0,000 for the F Test and partially tested the variable Age, Working Hours, Capital and Labor. This shows the variables of Age, Working Hours, Capital and Labor simultaneously and partially all the variables have a significant effect on the Traders Traditional Market Revenue of Trench 2, Tungkal Ilir District, Tanjung Jabung Barat Regency. Determination Coefficient (R2) value of 0.808 indicates that the influence of Age, Working Hours, Capital and Labor on the income of Traders of Traditional Market Trench 2, Tungkal Ilir District, Tanjung Jabung Barat Regency is 80.8%.